A case report of pulmonary cryptococcosis presenting as endobronchial obstruction - Zhou, Qing; Hu, Bijie; Shao, Changzhou; Zhou, Chunmei; Zhang, Xing; Yang, Dong; Li, Chun (Journal of Thoracic Disease, 2013)
Cryptococcosis presenting as endobronchial obstruction was scarce. We report a case of patient with cryptococcosis. A chest CT scan showed masses in the right upper lobe and right hilar, with evidence of narrowing of the right upper lobe bronchus. PET-CT scans showed the mass in the bronchus with the high mSUVs. A biopsy specimen was taken from the mass by lung puncture biopsy and showed cryptococcus infection. Culture of lung tissue was C. neoformans. The serum was positive for cryptococcal antigen, with a titer of more than 1:1,280. He was successfully treated using amphotericin B liposome. This case is worth discussing because it was cryptococcosis presenting as endobronchial obstruction that is often considered tumor.